2021
DOI: 10.1111/bph.15291
|View full text |Cite
|
Sign up to set email alerts
|

Zafirlukast is a broad‐spectrum thiol isomerase inhibitor that inhibits thrombosis without altering bleeding times

Abstract: Background and Purpose: Multiple members of the thiol isomerase (TI) family of enzymes are present in and released by platelets. Inhibition of these enzymes results in diminished platelet responses, aggregation, adhesion and thrombus formation.Recently, the therapeutic potential of TI inhibition has been recognised and drugdevelopment technologies were used to identify selective small molecule inhibitors.To date, few pan-TI inhibitors have been characterised and the most studied, bacitracin, is known to be nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
1
11
0
1
Order By: Relevance
“…Zafirlukast inhibits both in vitro platelet activation and in vivo thrombus formation without prolonging bleeding time in mice (Holbrook et al, 2020).…”
Section: Pdi Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zafirlukast inhibits both in vitro platelet activation and in vivo thrombus formation without prolonging bleeding time in mice (Holbrook et al, 2020).…”
Section: Pdi Inhibitorsmentioning
confidence: 99%
“…Notably, zafirlukast, a cysteinyl LT receptor antagonist used in the treatment of asthma, has been recently reported as a broad‐spectrum inhibitor for thiol isomerases including PDI, ERp57, ERp5 and ERp72. Zafirlukast inhibits both in vitro platelet activation and in vivo thrombus formation without prolonging bleeding time in mice (Holbrook et al, 2020).…”
Section: Pdi Inhibitorsmentioning
confidence: 99%
“…Our results were consistent with the study by Park et al (2019) , which showed that the combination of polymyxin and rifampicin has been used successfully against polymyxin-resistant A. baumannii pneumonia. Bacitracin is a peptide antibiotic, it’s parenteral administration is highly restricted due to its nephrotoxicity, which prohibits its systemic therapeutic usage ( Holbrook et al, 2021 ). Therefore, bacitracin is commonly used in combination with polymyxin and neomycin as triple antibiotic ointment for the topical treatment of wound infections ( Sierra et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we have recently shown that the cysteinyl LT receptor antagonist zafirlukast is a pan inhibitor of thiol isomerases, decreasing the reductase activity of PDI, ERp5, ERp57, ERp72 and TRX at micromolar concentrations 138 . Similar concentrations of zafirlukast were able to inhibit platelet aggregation, activation, calcium mobilization and in vivo thrombosis with no effect on bleeding time 138 . Therefore, there are currently few small molecule inhibitors of PDI and other thiol isomerases with well-described effects in thrombosis and haemostasis.…”
Section: Small Molecule Inhibitorsmentioning
confidence: 98%